WHEN DOES THE ANTHROCOSMIC MEDIA AGE BEGIN? - Juszczak, Mark Darius (Society Register, 2017)
The Google Lunar X Prize, which ends on December 31, 2017, has the potential to generate the first true instance of anthrocosmic media – media intended for consumption in outer space, which serves as a form of capital for an emergent autonomous field in the same. Winning the bonus segment of the X Prize consists of creating multimedia (photography or video) of one of the Apollo Landing Sites on the lunar surface. Both the terms of the creation of that media, and the media itself, are the first instances of agents acting to establish autonomy on the lunar surface – controlling how artifacts are accessed, used and represented. This paper is an exploration of the conditions required for the emergence of an anthrocosmic media age – an age where agents use media as a form of power in outer space to establish autonomy in fields that are also in outer space.